Affective prosody in European Portuguese: Perceptual and acoustic characterization of one-word utterances - Filipe, Marisa G. (2016)
A perceptual and acoustic characterization was provided on the expression of liking and disliking in the European Portuguese language. Thirty participants identified vocal patterns and judged the intensity of expressed affect in one-word items recorded by six untrained speakers. Listeners consistently associated vocal profiles with the two emotional patterns of liking and disliking. However, liking intonation was easier to recognize than disliking intonation. The feature most commonly associated with liking intonation was a wider and higher F0 pattern and a rising-falling contour. For disliking, the results revealed a flatter melodic pattern with a fall into the stressed syllable yielding a low plateau. In sum, both prosodic patterns showed different and consistent correlates.